Fatimeh Sayyah and Comparative Literature in Iran, Another Reflection - Alireza Anushiravani (مطالعات بین‌رشته‌ای ادبیات، هنر و علوم انسانی)
Golbon (1935-2013) is the first compiler who collected all the writings of Fatimeh Sayyah (1902-1948), a Russian-born Iranian literary scholar, and published them in one volume based on the recommendation of A. Sami'i. In this book, he calls her "the founder of Comparative Literature in Iran". I have shown that this is a wrong assumption. Although I appreciate her efforts in the development of literary studies, Golbon, who was not familiar with the basic tenets of Comparative literature, had mistakenly made an unsubstantiated claim. Based on the theories of Comparative Literature I have analyzed the discourse and the content of Sayyah's writings. Golbon was a cataloger and did not have any solid conception of Comparative Literature. Sayyah herself never claimed that she is a comparatist and, in fact, her education was on French literature in Moscow University. Besides, She was not even familiar with her contemporary Russian comparatists including Veselovsky and Zhimunsky.What is important is that Golbon's wrong assumption has had a negative influence on the future generations of Iranian comparatists, i.e. anybody with the least familiarity with Comparative Literature, has, thus, entered this rather new discipline and, as a result, has made grave misunderstandings on the nature and function of comparative studies in Iran. Thus after almost seventy years, Comparative Literature, under the auspices Persian Literature, has not been able to burgeon and achieve a prominent position internationally which it deserves.